Integrin β2 and β3: Two plasmatocyte markers deepen our understanding of the development of plasmatocytes in the silkworm Bombyx mori. (10th May 2022) - Zhang, Kui; Su, Jingjing; Hu, Xin; Yan, Xiaomin; Chen, Siyuan; Li, Chongyang; Pan, Guangzhao; Chang, Hongbo; Tian, Wenli; Abbas, Muhammad Nadeem; Cui, Hongjuan
Abstract: Insect hemocytes play important biological roles at developmental stages, metamorphosis, and innate immunity. As one of the most abundant cell types, plasmatocytes can participate in various innate immune responses, especially in encapsulation and node formation. Here, 2 molecular markers of plasmatocytes, consisting of integrin β 2 and β 3, were identified and used to understand the development of plasmatocytes. Plasmatocytes are widely distributed in the hematopoietic system, including circulating hemolymph and hematopoietic organs (HPOs). HPOs constantly release plasmatocytes with high proliferative activity in vitro ; removal of HPOs leads to a dramatic reduction in the circulating plasmatocytes, and the remaining plasmatocytes gradually lose their ability to proliferate in vivo . Our results demonstrated that the release of plasmatocytes from HPOs is regulated by insulin‐mediated signals and their downstream pathways, including PI3K/Akt and MAPK/Erk signals. The insulin/PI3K/Akt signaling pathway can significantly irritate the hematopoiesis, and its inhibitor LY294002 could inhibit the hemocytes discharged from HPOs. While the insulin/MAPK/Erk signaling pathway plays a negative regulatory role, inhibiting its activity with U0126 can markedly promote the discharge of plasmatocytes from HPOs. Our results indicate that the circulating plasmatocytes are mainly generated and discharged by HPOs. This process is co‐regulated by the PI3K/Akt and MAPK/Erk signals in an antagonistic manner to adjust the dynamic balance of the hemocytes. These findings can enhance our understanding of insect hematopoiesis. Abstract : Integrin β2 and β3 were considered as markers of plasmatocytes Circulating plasmatocytes originate from hemopoietic organ PI3K signals could positively regulate silkworm hematopoiesis MAPK signals could negative regulate silkworm hematopoiesis Crosstalk between MAPK and PI3K signals co‐regulate silkworm hemocytes balance